Determinants of Environmental Quality in Yogyakarta: Panel-Data Approach - Salwa Nabella Aksi Humanita; Ibnu Muhdir; Khoiruddin, Akhmad Yusuf (Jurnal Magister Ekonomi Syariah, 2024)
Environmental degradation is an important issue that currently challenges the continuity of sustainable economic development in a big city like Yogyakarta. This study analyzes what factors affect environmental quality. By using annual panel data from 2017-2023 in Yogyakarta City and proposing Panel Data Regression Analysis as the analysis method. The results show that GDP and Education have a positive effect on Environmental Quality, Population has no significant effect on Environmental Quality, and Tourists have a negative effect on Environmental Quality. An increase in per capita income and getting a proper education will improve the quality of the environment. However, the increase in population has no effect because public awareness still needs to be improved in environmental conservation efforts. Tourists increase consumption, so environmental pollution is getting higher. The implications of this research are useful for the government to develop policies that focus on raising awareness and stricter environmental regulations in Yogyakarta.